ANALISIS PENGARUH BELANJA DAERAH TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN MIMIKA - Salbia Taher; Antje Tuasela (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2019)
This study aims to analyze the effect of regional expenditure on economic growth in Mimika Regency. The research used comparative causal method, which intended to measure the effect or investigate the effects caused by the independent variable (regional expenditure) to the dependent variable (economic growth). Data collected by interview techniques, literature study and documentation. To determine the effect of regional expenditure on economic growth in Mimika Regency, a simple linear regression analysis tool is occupied. The results showed that there was no significant correlation between regional expenditure and economic growth.. Bivariate Person correlation analysis results show r-count value (0.371) <r-table value (0.632) then Ho is accepted, meaning that there is no significant correlation between regional expenditure with economic growth in Mimika Regency. This indicates that the fiscal policy of the regional government through the Mimika Regency APBD, especially in the aspect of regional expenditure has not been able to significantly encourage economic growth of the Mimika Regency